Reserve accumulation, inflation and moral hazard: Evidence from a natural experiment - Livia Chiţu (European Central Bank (ECB), 2016)
This paper assesses whether international reserve accumulation can be inflationary because of moral hazard and incentive effects. It tests the hypothesis that an increase in international reserves may incentivise countries to become complacent and pursue less prudent policies due to the perceived safety provided by higher reserve holdings. The paper uses a unique natural experiment to solve the endogeneity problem between reserve accumulation and macroeconomic developments, namely the 2009 general allocation of Special Drawing Rights (SDR). This allocation –the first one in almost three decades– enables to cleanly trace the effect of an unanticipated, global exogenous shock to the reserve holdings of the 186 IMF member countries. Difference-in-differences and propensity score matching estimates suggest that inflation in countries receiving large SDR allocations was about half a percentage point higher in annual terms within the next two years following the allocation, controlling for the standard arguments of the Phillips curve and other determinants. This effect is commensurate to the size of discretionary fiscal deficits in these countries, which is also consistent with the hypothesis that reserve accumulation may be inflationary because of moral hazard and incentive effects.
Keywords: F30; 330; difference-in-differences; international reserves; moral hazard; natural experiment; propensity score matching estimates; special drawing right